(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2024)
The relationship between native administration and tribes in Darfur during the period 1916-1956 was complex and multifaceted, This unique investigates this persuasive relationship, characterized by both participation and struggle. The foundation of local organization by the British colonial organization is inspected, in conjunction with its part in keeping up arrange and executing colonial approaches. The point of view of tribal resistance to this framework and the coming about pressures are too analyzed. The unique highlights the advancing flow of this relationship, molded by colonial control, patriot developments, and neighborhood control battles.